Wiley Encyclopedia of Composites 2012
DOI: 10.1002/9781118097298.weoc244
|View full text |Cite
|
Sign up to set email alerts
|

Surface Analysis

Abstract: Surface analysis has played an important role in the development of many advanced materials, including composites. This article describes the principles and instrumentation of the three most widely used surface analysis techniques: X‐ray photoelectron spectroscopy (XPS), Auger electron spectroscopy (AES), and time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS). Applications of these techniques in composites have been highlighted using some typical examples published recently. The strengths and weaknesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…In particular, the matrix effects, i.e., that secondary ion yields are strongly dependent on the matrix, are the main obstacle to quantitative analysis. However, the experimental results acquired during the past years have shown that semi-quantitative analysis of polymer blends or copolymers is possible [15,28,29]. In those cases, if the secondary fragments are correctly selected, matrix effects are negligible and the intensity of a fragment of a copolymer or polymer blend is a linear addition of the intensities of the same fragment from different components: Ii=truekjixj where Ii is the intensity of fragment i of a copolymer or polymer blend, kji is the sensitivity factor of fragment i of component j , and xj is the molar fraction of component j .…”
Section: Time-of-flight Secondary Ion Mass Spectrometrymentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, the matrix effects, i.e., that secondary ion yields are strongly dependent on the matrix, are the main obstacle to quantitative analysis. However, the experimental results acquired during the past years have shown that semi-quantitative analysis of polymer blends or copolymers is possible [15,28,29]. In those cases, if the secondary fragments are correctly selected, matrix effects are negligible and the intensity of a fragment of a copolymer or polymer blend is a linear addition of the intensities of the same fragment from different components: Ii=truekjixj where Ii is the intensity of fragment i of a copolymer or polymer blend, kji is the sensitivity factor of fragment i of component j , and xj is the molar fraction of component j .…”
Section: Time-of-flight Secondary Ion Mass Spectrometrymentioning
confidence: 99%
“…This relation has been used to perform quantitative analyses for some copolymers and polymer blend systems [15,28,29]. …”
Section: Time-of-flight Secondary Ion Mass Spectrometrymentioning
confidence: 99%
See 2 more Smart Citations
“…The cleanliness of graphene surfaces is important for successful uses of graphene in these applications. Surfaces of highly oriented pyrolytic graphite (HOPG), which can be regarded as the surfaces of defect-free graphene and surfaces of graphene were characterized by two very powerful surface analysis techniques -X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS) [1][2][3][4]. XPS results indicated that the impurities on the surfaces of graphene and HOPG can be removed by annealing samples of graphene and HOPG in vacuum at 400 o C [5].…”
Section: Extended Abstractmentioning
confidence: 99%